Quality of midwifery care in Soroti District, Uganda - Kaye, D (East African medical journal, 2000)
To determine the quality of care provided by midwives in Soroti district; and specifically, to identify training needs, gaps in knowledge and other barriers to accessibility of emergency obstetric care (EmOC) services in Soroti district. Cross-sectional descriptive study. One regional hospital, one district hospital, two health centres and four dispensaries, all health units in the district. Patients admitted in the health units with pregnancy complications; attendants of patients (above); midwives delivering health care at the health units; pregnant women exiting from (after attending) antenatal clinics; and health unit records. Participatory observation, midwife and client interviews, records review, facility assessment and focus group discussions with clients and patients. Ability of midwives to provide antenatal care of a minimum standard, or recall causes, signs, symptoms or the management of common obstetric complications; and patients and patient attendants' perception of care received. Many midwives were providing care of poor quality for both antenatal and delivery care due to their inability to identify and manage women with or at risk of pregnancy complications. The main factors identified as responsible for the poor quality of care were inadequate pre-service and in-service training, lack of technical support supervision and absence of standard treatment guidelines.